INTEGRATED SURGICAL AND REHABILITATION APPROACH IN NEONATAL INTESTINAL OBSTRUCTION - Azizov, Mamatkul; Ochilov, Ulugbek; Khushbakov, Khamza (International Conference on Arts, Society & Humanities, 2026)
Neonatal intestinal obstruction requires prompt surgical correction and effective postoperative recovery strategies. This study analyzed 150 neonates divided into a study group (n=91) and a reference group (n=59). The study group received a combined protocol integrating tailored surgical techniques with structured rehabilitation, including early enteral nutrition and gastrointestinal stimulation. Outcomes assessed included complication rates, recovery time, and hospitalization duration. The integrated approach reduced complications from 44.3% to 27.5%, shortened hospital stay by 5.9 days, and improved early intestinal function. These findings highlight the importance of combining surgical precision with rehabilitation to enhance neonatal recovery outcomes significantly.